Anti-Wear Design of the Knot-Tripping Mechanism and Knot-Tying Test for the Knotter - Shiyu Lv; Yaming Chen; Jianjun Yin; Maile Zhou; Zefu Chen (Lubricants, 2023)
Aiming to solve the problem of knot-tripping failure caused by severe wear between the spherical roller and planar cam of the knotter, this paper first establishes a calculation model of the spatial cam contour surface. The knot-tripping mechanism in the knotter is designed as a line-contact curved-surface cam mechanism, with the cutter arm swinging in accordance with sinusoidal acceleration. The design significantly reduces the contact stress between the cam and the roller, compared to the original knot-tripping mechanism. Additionally, it eliminates the impact between the spherical roller and the planar cam. Based on the Archard model, the calculation model for cam-roller wear in the knot-tripping mechanism has been derived and utilized for wear calculation. The wear test results of the knot-tripping mechanism with an aluminum cam show that the curved cam has a wear amount that is 43%, 56%, 46%, and 37% lower than that of the planar cam after tying the knot 200 times, 600 times, 1300 times, and 2000 times, respectively. Under the condition that the twine tension is set to 120 N, and the rotation speed of the fluted disc is 60 rpm, the deviations between the calculated value and the measured value of the wear amount of the curved cam are 9.48%, 6.01%, 7.27%, and 9.95%, respectively. This validates the accuracy of the spatial cam wear model and the correctness of the curved cam design.